2020
DOI: 10.1096/fj.201902746r
|View full text |Cite
|
Sign up to set email alerts
|

High‐fat diet induces endoplasmic reticulum stress to promote chondrocyte apoptosis in mouse knee joints

Abstract: Mice fed a high‐fat diet (HFD) become obese and develop osteoarthritis (OA)‐like lesions, including chondrocyte apoptosis, in the knee joints. However, the mechanism by which HFD/obesity induces chondrocyte apoptosis is not clearly understood. In the present study, male mice were fed a low‐fat diet (LFD, 10% kcal), HFD (45% kcal), or a HFD administered with 0.5 g/kg bodyweight of 4‐phenyl butyric acid (PBA, a small chaperone known to ease endoplasmic reticulum [ER] stress), via the drinking water. At the end o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 50 publications
(135 reference statements)
0
23
0
Order By: Relevance
“… 38 , 39 Our histological and behavioral observations confirmed that rats fed a HFD presented OA-like lesions, consistent with our previous and others’ studies. 40 , 41 Previously, oral administration of curcumin was shown to be effective in slowing the progression of OA in a post-traumatic OA mouse model. 42 However, doubts have been raised regarding whether oral curcumin can reach pharmacologically active concentrations in synovial fluid or joint tissues 43 and the oral bioavailability of curcumin is only 1%.…”
Section: Discussionmentioning
confidence: 99%
“… 38 , 39 Our histological and behavioral observations confirmed that rats fed a HFD presented OA-like lesions, consistent with our previous and others’ studies. 40 , 41 Previously, oral administration of curcumin was shown to be effective in slowing the progression of OA in a post-traumatic OA mouse model. 42 However, doubts have been raised regarding whether oral curcumin can reach pharmacologically active concentrations in synovial fluid or joint tissues 43 and the oral bioavailability of curcumin is only 1%.…”
Section: Discussionmentioning
confidence: 99%
“…OA, typified by joint space narrowing and a degenerative loss of cartilage integrity, is a dominant reason for disability, pain, and shortening of adult working life [17]. Interestingly, there is evidence showing that apoptosis is progressively recognized as a crucial driver of OA cartilage pathology [18,19]. Dysregulated gene expression in chondrocytes is implicated in the apoptosis and proliferation of chondrocytes, emphasizing the functional role of miRNAs in controlling chondrocyte apoptosis and development of OA [9,20].…”
Section: Discussionmentioning
confidence: 99%
“…40 More recently, HFD-induced obesity has been shown to induce osteoarthritis-promoting ER stress in mice, further highlighting the importance of considering the contribution of ER stress to the progression of metaflammation in the context of obesity. 41 Consistent with these discoveries, a significant increase in ER stress markers associated with adipose tissue inflammation appears in mice after 16 weeks of an HFD, which can be reversed by the administration of chemical chaperons. 42 Indeed, ER stress is known to induce the activation of the unfolded protein response (UPR), which aims at restoring cell function and production of adequatly folded proteins by using chaperons.…”
Section: Novel Concepts In Metaflammation the Nlrp3 Inflammasome: A Smentioning
confidence: 60%